1981
DOI: 10.2337/diab.30.6.486
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Survival in Patients with Diabetes Mellitus

Abstract: Platelet survival by 51chromium labeling was determined in six normal control subjects and in twelve patients with diabetes mellitus, before and after improved glucose control (mean HbA1c 10.5 +/- 2.2% and 7.1 +/- 1.8%, respectively). Mean platelet survival was 9.47 +/- 0.85 days for the normal subjects and 9.04 +/- 1.40 and 9.90 +/- 1.05 for the diabetic subjects in hyperglycemic and improved glycemic states, respectively. The differences between these values were not statistically significant. However, plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…Our results may expand on earlier findings on asso- ciations between PCs and MS (5) or insulin resistance (4). A few studies have suggested that a shorter platelet lifespan in patients with diabetes mellitus and atherosclerosis leads to increased PCs through a more active platelet production mechanism (24)(25)(26). In general, peripheral PCs depend on several complex factors (e.g., platelet survival, platelet production rate, and the exchangeable splenic platelet pool) (23).…”
supporting
confidence: 81%
“…Our results may expand on earlier findings on asso- ciations between PCs and MS (5) or insulin resistance (4). A few studies have suggested that a shorter platelet lifespan in patients with diabetes mellitus and atherosclerosis leads to increased PCs through a more active platelet production mechanism (24)(25)(26). In general, peripheral PCs depend on several complex factors (e.g., platelet survival, platelet production rate, and the exchangeable splenic platelet pool) (23).…”
supporting
confidence: 81%
“…Third, the biological plausibility of this association between platelet count and MetS may depend on insulin resistance. Platelet lifespan is known to be shorter in patients with insulin resistance [25]. Circulating TPO level involved in hyperglycemia, hyperinsulinemia, and insulin resistance, resulting enhanced platelet activation [26].…”
Section: Discussionmentioning
confidence: 99%
“…910 ' 2830 - 32 In addition, we and others have found a shortened life span of platelets in patients with Rd, again suggesting an increased turnover of platelets. 101433 " 35 Surprisingly, not only the "aggregatory pathways" of plate-lets seemed to be more active in relation to Rd, but also the anti-or disaggregatory system of prostacyclin-stimulated adenylate cyclase. There was a close correlation of ADPinduced platelet aggregation in vitro with prostacyclin-stimulated adenylate cyclase activity of platelets.…”
Section: Discussionmentioning
confidence: 99%